The Transformations of Values and Aspirations by Adventure Tourism in Nepal: example through the figures of three Sherpa - Raspaud, Michel (2014)
The purpose of this article is to analyze, through the figures and careers of three distinguished Sherpa (Ang Tharkay, Tenzing Norgay, and Sonam Sherpa), the transformation of values, perceptions and ways of thinking about their "Sherpa" profession (carrying high altitude). To do this, we use their published autobiographies and biographies, as well as the literature on mountaineering in theHimalayas. We demonstrate that, during the twentieth century, although the Sherpa of Khumbu Valley have experienced the same type of childhood (no school in their villages, work in the fields and care for animals), their aspirations changed, following the rhythm of the multiplication of the expeditions to peaks and the development of trekking activity, participating in the construction of new lifestyles and worldviews.